Motivasi Kerja Ditinjau dari Kontrak Psikologis pada Karyawan - Elvira Hardy; Diny Atrizka; Rianda Elvinawanty (Psyche 165 Journal, 2020)
This study aims to know the relationship between the psychological contract with work motivation. The subjects that used in this study are employee at PT. Sumtek Medan, in which the population consists of 110 employee. Data obtained from the scale to measure psychological contract and work motivation. The calculation of the datas began by doing a test prerequisite analysis (the test of assumptions) that consists of a test of normality and a test of linearity. The results of analysis showed the correlation coefficient at 0.762 of the significance 0.000 (p < 0.05). This shows there is a positive relationship between psychological contract with work motivation. The results of this study indicate that the variable of work motivation can be predicted by psychological contract at 58.1 percent and 88.9 percent of the rest are influenced by other factors which not examined in this study. Based on the results of this study, the hypothesis of there is a positive relationship between psychological contract with work motivation is accepted.